2016
DOI: 10.4187/respcare.04821
|View full text |Cite
|
Sign up to set email alerts
|

The 1-Minute Sit-to-Stand Test in Adults With Cystic Fibrosis: Correlations With Cardiopulmonary Exercise Test, 6-Minute Walk Test, and Quadriceps Strength

Abstract: BACKGROUND: Exercise testing is part of the regular assessment of patients with cystic fibrosis (CF). We aimed to evaluate (1) the convergent validity of the 1-min sit-to-stand (STS) test in CF by investigating its relationships with peak oxygen uptake (peak V O 2 ), quadriceps strength, and quality of life and (2) to compare these associations with those of the 6-min walk test (6MWT). METHODS: Twenty-five adults with CF (FEV 1 ‫؍‬ 59 ؎ 24%) performed the STS test, the 6MWT, quadriceps strength assessment, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 27 publications
(45 reference statements)
9
37
3
1
Order By: Relevance
“…Our data confirm that the 1-min STS test is able to detect oxygen desaturation [15], but to a lesser extent and less precisely than an exhaustive cycle ergometry CPET. Gruet et al [15] showed significant oxygen desaturation (defined as drop in SpO 2 N 4% from rest to peak exercise) during the 1-min STS test in adults with CF. They reported very strong correlations between [20] and Watt max [23].…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Our data confirm that the 1-min STS test is able to detect oxygen desaturation [15], but to a lesser extent and less precisely than an exhaustive cycle ergometry CPET. Gruet et al [15] showed significant oxygen desaturation (defined as drop in SpO 2 N 4% from rest to peak exercise) during the 1-min STS test in adults with CF. They reported very strong correlations between [20] and Watt max [23].…”
Section: Discussionsupporting
confidence: 60%
“…The continuous measurement of SpO 2 is recommended during exercise testing in CF [1] and oxygen desaturation (defined as SpO 2 b 90%) during exercise testing predicts pulmonary function decline and the number of hospitalization days over the subsequent 12 months in CF [27]. Our data confirm that the 1-min STS test is able to detect oxygen desaturation [15], but to a lesser extent and less precisely than an exhaustive cycle ergometry CPET. Gruet et al [15] showed significant oxygen desaturation (defined as drop in SpO 2 N 4% from rest to peak exercise) during the 1-min STS test in adults with CF.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations